The prognostic value of the central location of pulmonary nodules in osteosarcoma patients - Gehad Ahmed; Maged Elshafiey; Marwa Romeih; Ahmed Kamel; Ahmed Elgammal; Asmaa Salama; Yomna AboTabl; Mohammad Taher (Discover Oncology)
Abstract Background Most metastatic osteosarcoma pulmonary nodules exist in the periphery of the lung, while other lesions are close to the airway and vascular branches in the center. Central lesions require anatomical resection. However, there is a scarcity of data on the prognostic value of the central location of pulmonary metastasis in osteosarcoma. Methods We reviewed the medical records of osteosarcoma patients with metastasectomy between January 2009 and June 2022. The central lesions were identified as lesions requiring lobectomy or segmentectomy. We divided our cohort into Group A (peripheral lesion) and Group B (central lesion). The primary outcome measures were overall survival (OS) and postmetastasectomy event-free survival (PMEFS). Results We identified a total of 204 osteosarcoma patients with pulmonary metastases. Among them, 162 patients underwent metastasectomy: Group A (n = 128, 80.6%) and Group B (n = 34, 19.4%). Group A had a 5-year overall survival rate (OS) of 36.6% ± 5.7%, whereas Group B had a 5-year overall survival rate of 17.5% ± 8.5%, with (p = 0.048). The 3-year PMEFS for peripheral and central lesions was 25.7 ± 5.1 and 11.8 ± 7.1, respectively, with (p = 0.034). Conclusion In Osteosarcoma patients who underwent metastasectomy, central pulmonary nodules are associated with lower OS and PMEFS. We recommend, however, to keep offering these patients the option of metastasectomy as a predictor of survival until a more effective treatment is approved.